The Public Health Family Impact Checklist: A Tool to Help Practitioners Think Family - Crandall, AliceAnn; Novilla, Lynneth Kirsten B.; Hanson, Carl L.; Barnes, Michael D.; Novilla, M. Lelinneth B. (Frontiers in Public Health, 2019)
Families are an important cornerstone of individual and community health across the lifecourse. Not only do families play a role in the development of health, but the family’s health is likewise influenced by individual health behaviors and outcomes. Therefore, to improve population health, public health programs must support families. Limited training in family science, as well as lack of instruments to help "think family", often result in Public Health practitioners feeling ill-equipped to develop programming that supports, targets, and/or involves a diverse range of families. Tools to help public health practitioners think family are limited. The Family Impact Checklist is one tool that may help improve the degree to which policies support families. The purpose of this study was to adapt the Family Impact Checklist specifically for use in public health programming efforts. Through a two-round Delphi approach comprised of 17 public health professionals, the Public Health Family Impact Checklist was developed. The adapted Checklist includes 14 items across four think family principles: family engagement, family responsibility, family stability and family diversity. We propose that this tool will help practitioners develop high impact, family-friendly programs that ultimately lead to improved individual and community health.